Pressure distribution calculations based on a finite element model for cross country skiers - Breitschädel, F.; Authén, K.; Muren, J. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Traditional laboratory measurements of cross country (XC) skis often include camber height measurements where a ski is placed upon a flat rigid plate and loaded with various weights. Such measurements are often time consuming and they provide just results from the chosen loads. The goal of this study was (1) to develop a new XC Ski Analyzer measurement device which can measure the flexural stiffness and (2) based on these results create a finite element (FE) model for a cross country ski. This model can be used for a number of different simulations like pressure distribution models between the ski and a flat surface.